Pengaruh CAR, LDR, BOPO, Profitabilitas terhadap Loan quality pada Perbankan Syariah di Indoensia - Catur Wahyudi; Mohammad Arridho Nur Amin; Fahmi Firmansyah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
Banking in Indonesia is one of the financial institutions that play an important role in the economy of a country, this is because banking is one of the financial systems that functions as a financial intermediary. Funds resulting from community mobility are allocated to various economic sectors and all areas in need quickly and accurately. The increase in the mobilization of public funds has not been served by the conventional banking system and to accommodate the need for banking services in accordance with sharia principles. The analytical technique that will be used in this study is to use multiple linear regression analysis techniques to obtain a comprehensive picture of the relationship between variables. CAR (Capital Adequacy Ratio) has no effect on loan quality at Islamic commercial banks, BOPO (Operational Costs and Operating Income) has no effect on loan quality at Islamic commercial banks, LDR (Loan Deposit Ratio) has no effect on loan quality at Islamic commercial banks, Profitability has no effect on loan quality in Islamic commercial banks.